Teaching research methods in political science - Bernstein, Jeffrey L. (Elgar guides to teaching., 2021)
"Teaching Research Methods in Political Science brings together experienced instructors to offer a range of perspectives on how to teach courses in political science. It focuses on numerous topics, including identifying good research questions, measuring key concepts, writing literature reviews and developing information literacy skills. Illustrating the ways in which research methods courses connect with wider topics in political science, contributors discuss how methodological considerations can result in recognition of previously silenced voices, and consider the civic education mission of research methods in political science. Chapters outline quantitative and qualitative methods, feminist methodologies and techniques for studying African-American politics, to review and demonstrate the many avenues that instructors of research methods courses might take. This crucial guide to teaching will benefit instructors of courses in research methods in political science, as well as faculty leaders instituting new courses in political science. Its theoretical insights into civic education will also be useful to scholars of education more broadly"--